Utilizing the TikTok App to increase confidence in late teenagers to late adults - Adventania Martahelan Date Doni; Ella Oktisaputri; Lara Lara; Beatrix Wea; Jeremiah Efata Papahang (Indonesian Institute for Counseling, Education and Theraphy, 2022)
TikTok is an audio-visual-based social media application that contains short videos of a certain duration, with interesting features such as the latest music, unique filters, comment fields, video stitch features and others. Usually TikTok videos contain tips & tricks, trending dances, knowledge and so on that can be made by yourself or others. Videos made by other people will pass through our fyp or TikTok app homepage, then we can watch and comment on them. This research was conducted to find out how the level of self-confidence possessed by individuals from adolescence to late adulthood, when making TikTok videos of ideals vs reality that happened to themselves. The research method used is research and development, the population in this study is TikTok users aged 17 to 25 years totaling 25 people. The data obtained were then processed and analyzed using Person Centered Therapy Theory by adapting the WDEP Technique from Reality Theory. The results showed that on average the subjects felt happy when making TikTok videos of ideals vs. reality because it had various benefits that made them realize that they had accepted the reality of life that had happened, and they felt confident with who they were today.